Impact of female sex and type 2 diabetes mellitus on in-hospital mortality among patients with acute coronary syndrome: a retrospective cohort study between 2015-2022 - Alejandra Guzmán Quiroga; Alexander Bustamante Cabrejo; José Caballero-Alvarado; Carlos Zavaleta-Corvera; Othoniel Burgos Chávez (Российский кардиологический журнал)
Aim. This study aimed to assess the influence of female sex and type 2 diabetes mellitus (T2DM) on in-hospital mortality among patients diagnosed with acute coronary syndrome (ACS) in the emergency department during the period 20152022, while also exploring the association of relevant laboratory factors.Material and methods. An observational, analytical, retrospective cohort study was conducted, focusing on patients diagnosed with acute coronary syndrome who had high-density lipoprotein (HDL) values measured. The study included a total of 196 patients, divided into diabetes and non-diabetes groups, totaling 98 patients in each.Results. Among the 196 patients with acute coronary syndrome, 181 survived, and 15 succumbed until hospital discharge. Statistically significant associations were identified between female sex (relative risk (RR): 3.52, 95% confidential interval (CI): 1.25-9.92, p=0.017) and T2DM (RR: 4.05, 95% CI: 1.51-10.85, p=0.005) withan increased risk of mortality in acute coronary syndrome patients. Notably, high HDL values did not exhibit a statistically significant association (RR: 0.88, 95% CI: 0.33-2.33, p=0.789). Subsequent multivariate analysis reaffirmed the significant association, indicating a 20% increased risk of death in patients with T2DM and acute coronary syndrome (RR: 1.2, 95% CI: 0.15-2.25, p=0.025).Conclusion. The study concludes that while elevated HDL levels are not associated with increased in-hospital mortality in acute coronary syndrome patients, T2DM emerges as a noteworthy factor influencing this outcome.